Mazhab Pendidikan Kritis; Proses Humanisasi Pendidikan - Musa Al-Fadhil (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2016)
Education is considered as one way to liberation from underdevelopment ability financially or as a means to maintain the financial strength of the family. It is undeniable that the financial matter is very important, especially to measure human well-being, but knowledge is too oriented towards the focal point that has already set the dehumanization of man. Freire criticized the too-oriented education at the focal point of financial and material alone. He calls in education nuanced "Bank style" of this, the students are collecting and storing certain amount of knowledge, but in the end the students themselves who "saved" because of poor creativity. Education is patterned like this think man is a static item that only serves as a storage container. Humans are considered not to have creativity and creativity. Critical education is one of the solutions in the education offered by the flow of critical education is education that emphasizes how to understand, criticize, manufacture, and use science as a tool to understand the reality of life and change it, so do not just know the knowledge alone. There is a processing and reproduction of ideas in it.